Analysis of Business Potential For Management of Faecal Sludge Using Black Soldier Flies Based on The Market-Driven Approach (Case Study: IPLT Duri Kosambi Jakarta City) - Hanna Maria Scriftura Sinaga; Ahmad Soleh Setiyawan (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Faecal sludge management is crucial in supporting sustainable development in urban areas. Regional Regulation No. 10 of 1991 regulates the role of Faecal Sludge Treatment Plant managers in facing challenges related to increasingly limited dry sludge storage capacity. Therefore, this research explores the potential for utilizing faecal sludge processing products such as maggot and Kasgot organic fertilizer. This research includes identification of the product supply chain, analysis of market acceptance, and financial analysis using Net Present Value (NPV) and Benefit Cost Ratio (BCR). In the Duri Kosambi IPLT case study, the processed sludge produced and not yet managed could reach 100 m3 per month. Through comprehensive management by IPLT managers, semi-dry processed sludge can be utilized and distributed via waste trucks to BSF farms in Jakarta City. Based on estimated calculations, the mud is used as animal feed (maggot) as much as 8 tons/month and Kasgot organic fertilizer (50 tons/month). Based on market acceptance, the market volume for faecal sludge management products reached IDR 169,091,699/ 100 m3 with a growth rate of 7% every month. The factors influencing aspects of market acceptance consist of 9 factors, with the highest indicators influenced by market demand variables. Faecal sludge management using BSF is financially feasible based on an NPV analysis of 1.2 billion/year and a BCR of 1.2.